Texture profile analysis of mango parthenocarpic fruits cv. ‘Ataulfo’ - Maldonado Astudillo, Yanik Ixchel; Cantú Guzmán, Ángel; Salazar, Ricardo; Jiménez Hernández, Javier (Revista Mexicana de Ciencias Agrícolas, 2019)
Seedless fruits are called parthenocarpic, in the mango they have a size two to three times smaller than normal fruits and a high content of sugars. They are called ‘mango niño’, have a low economic value because they do not meet the standards of the national and international market. The objective of this study was to characterize parthenocarpic fruits of mango cv. ‘Ataulfo’; through, a texture profile analysis (TPA), weight loss and soluble solids content (TSS). The parthenocarpic fruits (PF) showed a decrease in the textural characteristics until reaching maturity. However, in non-parthenocarpic fruits (NPF) the decrease was less pronounced. The PF showed a softer texture and the most significant parameters were hardness and chewiness. Weight loss and TSS content were higher during storage in PF, indicating pulp with greater sweetness at the end of storage. The results provide important information about the potential uses of the child mango. It is suggested that soft and sweet pulp can be used in applications such as the preparation of syrups to prepare beverages or mango concentrates.